2020
DOI: 10.26508/lsa.202000924
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of distinct brown adipocyte subtypes in C57BL/6J mice

Abstract: Brown adipose tissue (BAT) plays an important role in the regulation of body weight and glucose homeostasis. Although increasing evidence supports white adipose tissue heterogeneity, little is known about heterogeneity within murine BAT. Recently, UCP1 high and low expressing brown adipocytes were identified, but a developmental origin of these subtypes has not been studied. To obtain more insights into brown preadipocyte heterogeneity, we use single-cell RNA sequencing of the BAT stromal vascular fraction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…A key element of healthy adipose tissue expansion is de novo differentiation of adipocytes rather than storage of fat in already existing adipocytes 4,5 . However, recent data indicate the existence of multiple white [6][7][8][9] and brown 10,11 adipocyte subtypes that originate from distinct precursor populations. Thus, the type of de novo differentiating adipocytes could strongly affect the metabolic response of the organism to weight gain, as lipid storage capacity, as well as adipokine production differs between white adipocyte subtypes [6][7][8][9] .…”
mentioning
confidence: 99%
“…A key element of healthy adipose tissue expansion is de novo differentiation of adipocytes rather than storage of fat in already existing adipocytes 4,5 . However, recent data indicate the existence of multiple white [6][7][8][9] and brown 10,11 adipocyte subtypes that originate from distinct precursor populations. Thus, the type of de novo differentiating adipocytes could strongly affect the metabolic response of the organism to weight gain, as lipid storage capacity, as well as adipokine production differs between white adipocyte subtypes [6][7][8][9] .…”
mentioning
confidence: 99%
“…Whether this could reflect some variation in previously unidentified subtype heterogeneity among adipocytes at embryonic stages, or is due to variation in the differentiation states of cells within a single adipocyte population is not clear. qRT-PCR on Hoxa5 null sBAT revealed no effect on embryonic expression of recently-identified markers for subtypes of adult brown adipocyte ( Karlina et al, 2021 ), including Bin1, Tcf24, Eif5 or P2rx5 (not shown).…”
Section: Resultsmentioning
confidence: 82%
“…However, only high- Ucp1 expressing subtypes were found until a few days after birth ( Song et al, 2020 ), and we did not find significant differences in any subtype markers other than Ucp1 in Hoxa5 null embryos. It would be interesting to determine whether some of the recently discovered heterogeneity among BAT adipoctyes does develop pre-natally ( Song et al, 2020 ; Karlina et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of Cidea, Prdm16, Tmem26, and Ppargc1a, all markers for brown and beige adipocytes, was increased in scWAT of HDM-exposed HFD-fed mice. 58,59 A potential link between HDM-induced inflammation and increased thermogenic gene expression in scWAT is via the observed increase in IL-13 and IL-4 expression. This could activate eosinophils to secrete IL-4, which acts directly on Pdgfra + precursor cells to increase the proliferation and differentiation of beige/ thermogenic adipocytes.…”
Section: Discussionmentioning
confidence: 99%